Carbon materials for stable Li metal anodes: Challenges, solutions, and outlook - Qiongqiong Lu (Wiley, 2021)
Abstract Lithium (Li) metal is regarded as the ultimate anode for next‐generation Li‐ion batteries due to its highest specific capacity and lowest electrochemical potential. However, the Li metal anode has limitations, including virtually infinite volume change, nonuniform Li deposition, and an unstable electrode–electrolyte interface, which lead to rapid capacity degradation and poor cycling stability, significantly hindering its practical application. To address these issues, intensive efforts have been devoted toward accommodating and guiding Li deposition as well as stabilizing the interface using various carbon materials, which have demonstrated excellent effectiveness, benefiting from their vast variety and excellent tunability of the structure–property relationship. This review is intended as a guide through the fundamental challenges of Li metal anodes to the corresponding solutions utilizing carbon materials. The specific functionalities and mechanisms of carbon materials for stabilizing Li metal anodes in these solutions are discussed in detail. Apart from the stabilization of the Li metal anode in liquid electrolytes, attention has also been paid to the review of anode‐free Li metal batteries and solid‐state batteries enabled by strategies based on carbon materials. Furthermore, we have reviewed the unresolved challenges and presented our outlook on the implementation of carbon materials for stabilizing Li metal anodes in practical applications.